Stanje in priložnosti v slovenski lesnopredelovalni industriji s perspektive podjetij - Redek, Tjaša (Les (Ljubljana), 2026)
This paper analyses the current situation, key development challenges, and opportunities in the Slovenian wood-processing industry from the perspective of firms. The main objective of the study is to examine the differences between more and less successful firms, particularly with regard to digitalization, investment in intangible capital, development plans for 2026, and perceptions of obstacles in the business environment. The analysis is based on survey data collected in February and March 2026 among firms operating in industries C16 and C31. The results show that more successful firms demonstrate greater agility, a higher level of digitalization, and invest more in software, training, brands, design, and research and development. Less successful firms are more pessimistic about future performance and investment. Firms identify labour costs, raw material and energy prices, bureaucracy, and the shortage of adequately qualified labour as the main obstacles to their operations.
Keywords: agilnost podjetij; business environment; digitalizacija; digitalization; firm agility; firm performance; intangible capital; investicije; investment; lesnopredelovalna industrija; neotipljivi kapital; poslovno okolje; Slovenija; uspešnost podjetij; wood-processing industry